SARS-CoV-2 Proteome-Wide Analysis Revealed Significant Epitope Signatures in COVID-19 Patients - Schwarz, Tatjana; Heiss, Kirsten; Mahendran, Yuvaraj; Casilag, Fiordiligie; Kurth, Florian; Sander, Leif E.; Wendtner, Clemens-Martin; Hoechstetter, Manuela A.; Müller, Marcel A.; Sekul, Renate; Drosten, Christian; Stadler, Volker; et al. (Frontiers in Immunology, 2021)
The WHO declared the COVID-19 outbreak a public health emergency of international concern. The causative agent of this acute respiratory disease is a newly emerged coronavirus, named SARS-CoV 2, which originated in China in late 2019. Exposure to SARS‑CoV‑2 leads to multifaceted disease outcomes from asymptomatic infection to severe pneumonia, acute respiratory distress and potentially death. Understanding the host immune response is crucial for the development of interventional strategies. Humoral responses play an important role in defending viral infections and are therefore of particular interest. With the aim to resolve SARS-CoV-2-specific humoral immune responses at the epitope level, we screened clinically well-characterized sera from COVID-19 patients with mild and severe disease outcome using high-density peptide microarrays covering the entire proteome of SARS-CoV-2. Moreover, we determined the longevity of epitope-specific antibody responses in a longitudinal approach. Here we present IgG and IgA-specific epitope signatures from COVID-19 patients, which may serve as discriminating prognostic or predictive markers for disease outcome and/or could be relevant for intervention strategies